Data analysis and mapping for monitoring health risk. What has the spread of the Covid-19 pandemic in northern Italy taught us? - Tiboni, Michela; Pezzagno, Michèle; Vetturi, David; Alexander, Craig; Botticini, Francesco (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The construction of the knowledge framework is a fundamental phase in the territorial governance process and data analyses, together with their mapping using GIS software, provide a fundamental basis for the structuring of a system for making decisions. With reference to the issue of risk management, monitoring of spatial and temporal evolution of the phenomena is equally fundamental. The aim of the paper is to address these issues in relation to health risk, starting from the pandemic situation that affected northern Italy in the early months of 2020. The paper presents an ex-post statistical analysis of the ISTAT data on mortality in the Italian provinces, comparing the currently available 2020 data to previous years. A territorial analysis is then presented, using a GIS, regarding the spread of the Covid-19 infection in the 205 municipalities of the province of Brescia. The paper also proposes a comparison with analysis conducted for other territories outside Italy. Finally, a reflection is offered on what we have learned from this pandemic regarding the need to have a monitoring system for phenomena related to health risk, in order to reduce the vulnerability of the health system.